Corrosion of Aluminum Components and Remedial Measures (Biological Sciences - PJSIR, 2006)
Aluminum has versatile physical properties, mechanical strength, corrosion resistance, and is used in special applications like aerospace, automobiles and other strategic industries. The outdoor exposed structural components of aluminum have very good corrosion resistance due to the thick oxide layer (0.2 - 0.4 m). This study involves the corrosion of aluminum based components, though aluminum is protected by an oxide layer but due to extreme weather and environ- mental conditions the oxide layer was damaged. The corroded product was removed, pits or cavities formed due to the material removal were filled with epoxy resins and acrylic-based compounds containing fibreglass as reinforcement. Optimum results were obtained with epoxy resins incorporated with 5% glass fibres. The inner surface of the components was provided further protection with a cellulose nitrate compound.